Longitudinal Analysis of Arterial Blood Pressure and Heart Rate Response to Acute Behavioral Stress in Rats with Type 1 Diabetes Mellitus and in Age-Matched Controls - Randall, David C.; Speakman, Richard O.; Silcox, Dennis L.; Brown, Laura V.; Brown, David R.; Gong, Ming C.; Patwardhan, Abhijit; Reynolds, L. R.; Karounos, Dennis G.; Burgess, Don E.; Anigbogu, Chikodi N. (Frontiers in Physiology, 2011)
We recorded via telemetry the arterial blood pressure (BP) and heart rate (HR) response to classical conditioning following the spontaneous onset of autoimmune diabetes in BBDP/Wor rats versus age-matched, diabetes resistant control (BBDR/Wor) rats. Our purpose was to evaluate the autonomic regulatory responses to an acute stress in a diabetic state of up to 12 months duration. The stress was a 15 sec. pulsed tone (CS+) followed by a 0.5 sec. tail shock. The initial, transient increase in BP (i.e., the ‘first component’, or C1), known to be derived from an orienting response and produced by a sympathetic increase in peripheral resistance, was similar in diabetic and control rats through 9 months of diabetes; it was smaller in diabetic rats 10 months after diabetes onset. Weakening of the C1 BP increase in rats that were diabetic for > 10 months is consistent with the effects of sympathetic neuropathy. A longer-latency, smaller, but sustained ‘second component’ (C2) conditional increase in BP, that is acquired as a rat learns the association between CS+ and the shock, and which results from an increase in cardiac output, was smaller in the diabetic vs. control rats starting from the first month of diabetes. A concomitant HR slowing was also smaller in diabetic rats. The difference in the C2 BP increase, as observed already during the first month of diabetes, is probably secondary to the effects of hyperglycemia upon myocardial metabolism and contractile function, but it may also result from effects on cognition. The small HR slowing concomitant with the C2 pressor event is probably secondary to differences in baroreflex activation or function, though parasympathetic dysfunction may contribute later in the duration of diabetes. The nearly immediate deficit after disease onset in the C2 response indicates that diabetes alters BP and HR responses to external challenges prior to the development of structural changes in the vasculature or autonomic nerves.